An interdisciplinary framework to optimize the anticipation skills of high-level athletes using virtual reality - Montagne, G.; Mascret, N.; Bossard, M.; Chomienne, L.; Ledouit, S.; Rao, G.; Tordi, N.; Verhulst, E.; Kulpa, R. (Frontiers in Sports and Active Living, 2024)
The ambition of our contribution is to show how an interdisciplinary framework can pave the way for the deployment of innovative virtual reality training sessions to improve anticipation skills in top-level athletes. This improvement is so challenging that some authors say it is like "training for the impossible". This framework, currently being implemented as part of a project to prepare athletes for the 2024 Olympic Games in Paris, based on the ecological-dynamics approach to expertise, is innovative in its interdisciplinary nature, but also and above all because it overcomes the limitations of more traditional training methods in the field designed to optimize anticipation skills in top-level athletes. The ambition is to tackle successive challenges ranging from the design of virtual partners and opponents to the deployment of training programs in virtual reality, while ensuring the acceptability and acceptance of such innovative virtual reality training protocols and measuring associated workloads.